2016
DOI: 10.1177/0269216315613902
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning in motor neuron disease: A qualitative study of caregiver perspectives

Abstract: Advance care planning can assist patients to achieve a sense of control and 'peace of mind' and facilitates important family discussion. However, the timing and style of its introduction needs to be approached sensitively. Tools and strategies for increasing the efficacy of advance care planning for motor neuron disease should be evaluated and implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 17 publications
5
80
0
2
Order By: Relevance
“…In fact, beyond the request for pain relief, this review found scarce insight into what medical options residents and family members considered important to include in ACP, and wide variability was found regarding the “right time” for ACP. These findings confirm the need for further studies and guidance regarding the timing and style of introducing ACP to patients and their families,38 with the consideration that choosing the right moment and appropriate wording to engage patients in ACP may have a profound impact on the value and effects of ACP 4…”
Section: Discussionsupporting
confidence: 61%
“…In fact, beyond the request for pain relief, this review found scarce insight into what medical options residents and family members considered important to include in ACP, and wide variability was found regarding the “right time” for ACP. These findings confirm the need for further studies and guidance regarding the timing and style of introducing ACP to patients and their families,38 with the consideration that choosing the right moment and appropriate wording to engage patients in ACP may have a profound impact on the value and effects of ACP 4…”
Section: Discussionsupporting
confidence: 61%
“…Timeliness of decision making is frequently raised in the broader MND literature. A discord is evident between people with MND and health care professionals or between people with MND and their family carers, with health care professionals and family carers often advocating for early or pre‐emptive decisions whilst people with MND, either because of denial or wishing of focus on the present, choosing to postpone decisions . The importance of early decision making is often justified due to the inevitable deterioration in speech function and possible development of cognitive deficits .…”
Section: Discussionmentioning
confidence: 99%
“…A discord is evident between people with MND and health care professionals or between people with MND and their family carers, with health care professionals and family carers often advocating for early or pre-emptive decisions whilst people with MND, either because of denial or wishing of focus on the present, choosing to postpone decisions. 10,36,46 The importance of early decision making is often justified due to the inevitable deterioration in speech function and possible development of cognitive deficits. 20,29 Early discussions with patients and carers are recommended in international clinical guidelines for MND, in order to establish advance care plans or because timing is crucial to some intervention decisions, such as gastrostomy, which has a defined window of opportunity.…”
Section: Amyotrophic Lateral Sclerosis and Assisted Ventilationmentioning
confidence: 99%
“…Although the end‐of‐life phase remains poorly defined and timing of palliative care input is not consistent globally, 22 advance care planning assists patients and their families with important decision making, imparting control and composure in a situation in which they may otherwise be absent. Carers have identified disease‐specific advanced directives (such as patient letters of future care) as useful tools to stimulate such discussion while maintaining respect for patient autonomy 23 . Appropriate timing for these discussions is often individually based, but can be sensitively approached when introducing intervention options such as non‐invasive positive pressure ventilation or gastrostomy.…”
Section: Advances In Treatment Approach: New Standards Of Carementioning
confidence: 99%